HPV16 E6 regulates annexin 1 (ANXA1) protein expression in cervical carcinoma cell lines - Calmon, Marilia Freitas [UNESP]; Sichero, Laura; Boccardo, Enrique; Villa, Luisa Lina; Rahal, Paula [UNESP] (Elsevier B.V., 2016)
Annexin 1 (ANXA1) is a substrate for E6AP mediated ubiquitylation. It has been hypothesized that HPV 16 E6 protein redirects E6AP away from ANXA1, increasing its stability and possibly contributing to viral pathogenesis. We analyzed ANXA1 expression in HPV-positive and negative cervical carcinoma-derived cells, in cells expressing HPV-16 oncogenes and in cells transduced with shRNA targeting E6AP. We observed that ANXA1 protein expression increased in HPV-16-positive tumor cells, in keratinocytes expressing HPV-16 E6wt (wild-type) or E6/E7 and C33 cells expressing HPV-16 E6wt. ANXA1 protein expression decreased in cells transfected with E6 Dicer-substrate RNAs (DsiRNA) and 03 cells co-transduced with HPV-16 E6wt and E6AP shRNA. Moreover, colony number and proliferation rate decreased in HPV16-positive cells transduced with ANXA1 shRNA. We observed that in cells infected with HPV16, the E6 binds to E6AP to degrade p53 and upregulate ANXA1. We suggest that ANXA1 may play a role in HPV-mediated carcinogenesis. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: HPV16; E6; ANXA1; P53; Cervical cell lines; Keratinocytes